Clinical outcomes following polymer-free sirolimus-eluting stent implantations in unselected patients: A descriptive subgroup analysis in patients with renal impairment. Issue 29 (17th July 2020) - Krackhardt, Florian; Waliszewski, Matthias W.; Kherad, Behrouz; Barth, Claudia; Marcelli, Daniele
Abstract : Abstract: Patients with chronic kidney disease (CKD are frequently excluded from coronary artery disease trials. The aim of this assessment was to study the clinical outcomes of polymer-free sirolimus-eluting stent implantations in patients with impaired renal function. Large-scale, international, single-armed, multicenter, 'all comers' observational studies (ClinicalTrials.gov Identifier: NCT02629575 and NCT02905214) were used for this post-hoc subgroup analysis to compare the clinical outcomes in patients with normal renal function (NRF) to those with renal insufficiency (CKD, dialysis dependence). The accumulated target lesion revascularization rate was the primary endpoint at 9 to 12 months whereas the accumulated major adverse cardiac event, stent thrombosis (ST) and procedural success rates were part of the secondary endpoints. There were 6791 patients with NRF, whereas 369 patients had CKD and 83 patients were dialysis dependent. The target lesion revascularization rate at 9 to 12 months was significantly higher in dialysis patients (2.1% vs 3.3% vs 6.7%, P = .011). The accumulated major adverse cardiac events rates in the dialysis and in the CKD group were significantly higher as compared to patients with NRF (13.3% vs 4.0%, P < .001; 6.5% vs 4.0%, P = .024). Finally, ST rates (NRF: 0.7%, CKD: 0.6%, dialysis: 1.3%) were not statistically different between subgroups ( P = .768). All-cause cumulative mortality rates were 3.3% (CKD) and 4.0% (dialysis) respectively. Percutaneous coronary interventions with polymer-free, ultra-thin strut sirolimus-eluting stents have comparable revascularization rates in CKD and dialysis dependent patients as compared to percutaneous coronary interventions with other 2nd generation drug-eluting stents. ST and all-cause mortality rates were low as compared to available literature references.